(untitled) (Journal of the College of Basic Education, 2025)
The objective of this research was to design and implement instructional units based on the cognitive modeling strategy using multimedia to teach selected fundamental football skills to students, and to determine the effectiveness of these units by evaluating the performance of experimental groups in the post-test. The researcher employed the experimental method due to its suitability for the research objectives and procedures, adopting an equivalent groups design. The research population was purposively selected from first-year students of the Department of Physical Education and Sports Sciences at Ashur University for the academic year 2024–2025, comprising 86 male and female students from the morning session.A total of 60 students were selected using systematic random sampling and were distributed into three experimental groups (Rooms A, B, and C), each consisting of 20 students. Female students were excluded, as football is taught only to male students. Additionally, students who were absent or actively participating in football clubs were excluded from the study.Ten students from Room A were selected for the pilot study. The field procedures included skill tests, followed by the pilot study to establish the scientific validity and reliability of the tests. Pre-tests were then administered to all three groups.Subsequently, the researcher prepared instructional units for the two experimental groups: one group received cognitive modeling instruction, and the other received cognitive modeling supported by multimedia. Each group underwent 10 instructional sessions, delivered once a week, each lasting 90 minutes.Following the implementation of the units, post-tests were administered to all groups. The results indicated that cognitive modeling using multimedia had a significant and positive impact on learning basic football skills, showing superior performance compared to traditional teaching methods.The researcher recommended that both public and private colleges adopt the findings of this study in their teaching plans and encourage the use of modern educational strategies such as cognitive modeling. Furthermore, the integration of interactive platforms like ThingLink in sports education—particularly football and other sports—was emphasized.